2011
DOI: 10.1007/s00586-011-1887-2
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral artery injuries following cervical spine trauma: a prospective observational study

Abstract: In patients with cervical spine fractures or dislocations crossing the course of the vertebral artery, VAI are relatively frequent and may be associated with significant morbidity and mortality. VAI were identified by DSA in 27.5%. Despite anticoagulation therapy, 5.8% became clinically symptomatic and 2.9% died due to cerebrovascular ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 46 publications
(75 reference statements)
1
52
0
5
Order By: Relevance
“…17 This may explain the relatively lower rates of VAI in our study (13%) compared with other published series. 1,2,7 Our data may be consistent with the hypothesis that injuries which result in vertebral artery transection may in fact be protective for posterior circulation infarction, if the collateral circulation is sufficient to prevent an acute stroke, by preventing later embolic events at the time of recanalisation. However, further studies will be required to investigate this further.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…17 This may explain the relatively lower rates of VAI in our study (13%) compared with other published series. 1,2,7 Our data may be consistent with the hypothesis that injuries which result in vertebral artery transection may in fact be protective for posterior circulation infarction, if the collateral circulation is sufficient to prevent an acute stroke, by preventing later embolic events at the time of recanalisation. However, further studies will be required to investigate this further.…”
Section: Discussionsupporting
confidence: 78%
“…[1][2][3] Rates of VAI associated with cervical spinal trauma vary significantly with the incidence ranging from 3 to 88% in the literature. Prospective studies suggest rates in the range of 17-27% 4-8 with a fatal outcome reported in rare cases.…”
Section: Introductionmentioning
confidence: 99%
“…Structurally, it occurs on fixed segment and mobile segment junctions. The C6 transverse foramen is the most common and the C1/2 site is the second most common 11). It is com-mon in children with V2 segments and adults with V3 segments 4).…”
Section: Discussionmentioning
confidence: 99%
“…Cothren et al 26 reported an overall CVA risk of 21% and advocated comprehensive screening, early diagnosis, and institution of early antithrombotic therapy for BCVI. 36 They documented no complications associated with either agent. 26 Mueller et al 36 treated 69 of 599 patients who sustained cervical spinal fracture and VAI.…”
Section: Jang Et Al 2011mentioning
confidence: 97%